Combat Flails in the Armament of the Golden Horde - Kuleshov Yu.A. (Золотоордынское обозрение, 2019)
Research objectives: To discuss, as far as possible, types of offensive weapons used in the Golden Horde. Materials: Combat flails are considered the research materials as a category of weapons that have not previously come into the analysis of specialists. Results and novelty of the research: Among researchers, it is generally accepted that combat flails were the exclusively weapons of non-professional soldiers who fought on foot. Accordingly, horsemen did not need to use such weapon. Moreover, as the results of the study showed, combat flails were part of the larger armaments of the Golden Horde’s warriors. In their hands it was a very formidable weapon. The novelty of the study lies in the expansion of our ideas about the weapons and warfare of the Golden Horde.